2017
DOI: 10.1155/2017/7059068
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Protection and Analgesic Activity of a Botanical Composition Comprised of Morus alba, Scutellaria baicalensis, and Acacia catechu

Abstract: Although there have been augmented advances in drug discovery, current OA management is inadequate due to the lack of successful therapies proven to be effective in modifying disease progression. For some, the risk outweighs the benefit. As a result, there is a desperate need for safe and efficacious natural alternatives. Here we evaluated a composition from Morus alba, Scutellaria baicalensis, and Acacia catechu in maintaining joint structural integrity and alleviating OA associated symptoms in monoiodoacetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…In previous studies, SBE-related studies have focused on baicalin, baicalein, and wogonin, and among them, baicalein was the most studied. Baicalein has been reported to have antibacterial, antiviral, and antioxidant effects and inhibit inflammatory cytokines [11,13,14,[26][27][28][29]. Therefore, the present study agrees with previous studies that have investigated whether inflammatory cytokines were suppressed.…”
Section: Jar Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous studies, SBE-related studies have focused on baicalin, baicalein, and wogonin, and among them, baicalein was the most studied. Baicalein has been reported to have antibacterial, antiviral, and antioxidant effects and inhibit inflammatory cytokines [11,13,14,[26][27][28][29]. Therefore, the present study agrees with previous studies that have investigated whether inflammatory cytokines were suppressed.…”
Section: Jar Discussionsupporting
confidence: 91%
“…Baicalin significantly inhibited IL and NO in LPS-stimulated RAW 264.7 cells [26] and have anti-inflammatory action while suppressing the activations of TNF-a, MAPK, and NF-κB without inducing cytotoxicity [27,28]. In addition, the complex extract of S. baicalensis, Morus alba, and Acacia catechu showed improvement in pain and recovery of damaged cartilage and reduction of C-terminal telopeptide of type II collagen (CTX-II) in urine in MIA-induced knee OA mice [29].…”
Section: Jar Discussionmentioning
confidence: 99%
“…It has also been suggested to provide improvement in cartilage matrix integrity. 33 These effects probably have translated to clinical benefits. A study from Arjmandi et al reported that the combination of extracts from two plants was associated with significant reduction in perceived pain, stiffness and mean range of motion after one-week treatment.…”
Section: Scutellaria Baicalensis and Acacia Catechu Extractsmentioning
confidence: 99%